Upaya Wali Kelas Dalam Meningkatkan Kedisiplinan Siswa (Studi Kasus Pada MTsN 11 Agam) - Arif Fiandi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the efforts of homeroom teachers in improving student discipline at MTsN 11 Agam. This study uses a descriptive qualitative approach. The data collection technique used in this research is observation by observing directly the phenomena that occur in the field, interviews with related parties such as homeroom teachers and documentation studies by examining documents related to the topic of this research discussion. The results of this study explain the efforts made by the homeroom teacher in improving student discipline at MTsN 11 Agam, namely: socializing the rules or regulations that apply to students, establishing cooperation with all school members and the community, especially parents of students, imposing sanctions on students who violate school rules, give awards to students who are always disciplined and have never been recorded as violating school rules.Â